About Possibility of Using New Organic Synthetic Selenium-Containing Compounds During Hypothermic Storage of Organs - ÐšÐ¾valenko, A. A.; Holubtsova, Maryna A.; Ðžvsyannikova, Tetiana M.; Dyachenko, B. D. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 190.